2014
DOI: 10.1074/mcp.m113.028969
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Lectin Affinity Based Plant N-Glycoproteome Profiling Using Tomato Fruit as a Model

Abstract: Lectin affinity chromatography (LAC) can provide a valuable front-end enrichment strategy for the study of N-glycoproteins and has been used to characterize a broad range eukaryotic N-glycoproteomes. Moreover, studies with mammalian systems have suggested that the use of multiple lectins with different affinities can be particularly effective. A multi-lectin approach has also been reported to provide a significant benefit for the analysis of plant N-glycoproteins; however, it has yet to be determined whether c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 71 publications
7
60
1
1
Order By: Relevance
“…Redox changes in the apoplast are likely to influence a wide range of cell wall-processing enzymes that have N-glycosylation sites, Cys thiols, and disulfide bonds. Posttranslational modifications of these enzyme proteins protect them from proteolytic degradation and provide accurate targeting of N-glycoproteins (Zielinska et al, 2012;Ruiz-May et al, 2014). While callose can be deposited in the cell wall around the plasmodesmata to plug the sieve plates and deter feeding (Will and van Bel, 2006), no significant changes in the expression of callose synthases or endo-1,3-b-glucanases were observed in our studies.…”
Section: Discussioncontrasting
confidence: 36%
“…Redox changes in the apoplast are likely to influence a wide range of cell wall-processing enzymes that have N-glycosylation sites, Cys thiols, and disulfide bonds. Posttranslational modifications of these enzyme proteins protect them from proteolytic degradation and provide accurate targeting of N-glycoproteins (Zielinska et al, 2012;Ruiz-May et al, 2014). While callose can be deposited in the cell wall around the plasmodesmata to plug the sieve plates and deter feeding (Will and van Bel, 2006), no significant changes in the expression of callose synthases or endo-1,3-b-glucanases were observed in our studies.…”
Section: Discussioncontrasting
confidence: 36%
“…Furthermore, CPLL may serve to increase the effectiveness of other technologies. For instance, in studies of the tomato pericarp N-glycoproteome, a high dynamic range of identified N-glycoproteins was found even after enrichment with lectin affinity chromatography (Ruiz-May et al 2014). Combining an affinity chromatography approach with CPLL may provide an alternative pipeline to reduce the high dynamic range of proteins with posttranslational modifications.…”
Section: New Technologies For Proteomics Studies In Somatic Embryogenmentioning
confidence: 99%
“…This versatile technique utilizes a broad range of ligands covalently linked to different types of matrixes (e.g., Sepharose, agarose, and others) (Zielinska et al 2012;Ruiz-May et al 2014). A wide variety of ligands is now commercially available including: antibodies used to enrich specific antigens, substrates to trap enzymes, ligands to isolate receptors, and lectins to enrich and characterize low abundance glycoproteins (Wilchek and Chaiken 2000;Steen et al 2006;Hage and Matsuda 2015).…”
Section: New Technologies For Proteomics Studies In Somatic Embryogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycoproteome has been analyzed from Arabidopsis (Lastovickova et al 2011;Zhang et al 2011;Minic et al 2007), barley grain (Lastovickova et al 2011), tomato (Catala et al 2011;Thannhauser et al 2013;Ruiz-May et al 2013), maize (Silva-Sanchez et al 2014), tobacco (Hruba and Tupy 1999), rice (Komatsu et al 2009), Brachypodium (Zhang et al 2014) and cotton (Kumar et al 2013). As glycosylation plays an important role in various biological processes including growth and development (Palmisano et al 2010).…”
Section: Introductionmentioning
confidence: 99%